THE QUALITY CONTROL OF ELECTROLYTIC TANTALUM CAPACITORS BY USING THE STRESS TEST - P. L. Kuznetsov; V. V. Muraviev (Приборы и методы измерений)
The article discusses the accelerated method of analysis the electrolytic tantalum capacitors quality on the basis of the change equivalent series resistance forecast while conducting the STRESS TEST.